Confirmation of Connexin45 Underlying Weak Gap Junctional Intercellular Coupling in HeLa Cells - Choi, Eun Ju (Biomolecules, 2020)
Gap junctions (GJs) are intercellular channels that connect adjacent cells electrically and metabolically. The iodide-yellow fluorescent protein (I-YFP) gap junctional intercellular communication (GJIC) assay is a recently developed method with high sensitivity. HeLa cells have been widely used as GJ-deficient cells for GJ-related research. Herein, we present evidence showing that HeLa cells have functional GJs comprising connexin (Cx) 45 using the I-YFP GJ assay and CRISPR/Cas9 system. We conducted the I-YFP GJIC assay in HeLa cells, which revealed a weak level of GJIC that could not be detected by the Lucifer yellow scrape-loading assay. The mRNA expression of GJB5 (Cx31.1), GJA1 (Cx43), and GJC1 (Cx45) was detected in HeLa cells by RT-PCR analysis. Knocking out GJC1 (Cx45) abolished GJIC, as analyzed by the I-YFP assay and dual whole-cell patch-clamp assay. These results suggest that HeLa cells express Cx45-based GJs and that the I-YFP GJIC assay can be used for cells with weak GJIC, such as Cx45-expressing HeLa cells. Further, GJC1 (Cx45)-knockout HeLa cells are more suitable as a GJ-null cell model for transfection experiments than wild-type HeLa cells. This experimental design was successfully applied to knock out Cx43 expression and GJIC in A549 lung cancer cells and can thus be used to identify major Cxs in other cell types and to establish GJ assay systems for different Cxs.